Socio-economic risk factors of household food insecurity and their population attributable risk: A population-based study - Asadi-Lari, Mohsen (Med J Islam Repub Iran, 2019)
Background: Food insecurity as a major public health problem has associations with a wide range of adverse consequences on health and quality of life. The aim of this study is to determine the prevalence of food insecurity among Iranian households, its key socioeconomic risk factors and population attributable risk via a large-scale cross-sectional study in the capital of Iran. Methods: This cross-sectional study was performed among 30,809 households with complete questionnaires of food security, during 2011. The univariate test was used to investigate the association between economic status and covariates with household food insecurity. Multiple logistic regression model was used to assess the independent effect of economic status on household food insecurity. Results: Totally, 37.8% (95% CI: 37.25, 38.34%) of the households were food insecure. There were significant associations between economic status and household food insecurity after adjustment for other variables (p-value<0.001). The extent of household food insecurity that could be attributed to the economic status in the 1st and 2nd quintiles (poorest and poor households), compared with the 5th quintile (richest households), was estimated to be 48.43% and 60.12%, respectively. Conclusion: Food insecurity is relatively prevalent among households in Tehran. Economic status was identified as the most significant determinant of household food security, as 62.7% of poorest households were food insecure. Therefore, there is a crucial need to address food insecurity as a priority in food policies.